Content Publishing Platform in the Web 3.0 Era——Mirror Case Study - Zhen, Liu; Prabhashini, Kumesh (Beijing Press, 2023)
With the development of technology and society, the content industry is facing many problems that Web2.0 cannot solve. With its characteristics of decentralization, emphasis on user value, and emphasis on user ownership and control, Web3.0 provides a new development opportunity for the digital publishing industry. The related blockchain technology and NFT based on blockchain technology are also Shine brilliantly in the content market. This article takes Mirror, a decentralized content publishing platform, as an example to analyze how to solve the current publishing problems from three aspects: decentralized content publishing, NFT ownership economic model and autonomous and open community, so as to enhance the understanding of publishing in the Web3.0 era. Cognition of platform function and form.
Web 3.0时代的内容出版平台 ——Mirror个案研究
Keywords: Web 3.0; blockchain; NFT; Mirror; digital publishing